Indonesian Teachers' Self-Efficacy on Implementation Cooperation and Class Management towards Inclusive Education - Ahsan Romadlon Junaidi; Oktaviani Hidayah; Ediyanto Ediyanto; Asep Sunandar (AL-ISHLAH: Jurnal Pendidikan, 2023)
In inclusive education, teachers' self-efficacy represents their self-assessment of the capability to organize classroom learning with students' various learning needs, including disabilities. The teacher's self-efficacy is observed in three aspects, namely instruction efficacy, collaboration efficacy, and managing behaviour. This study examines the effects of differences in working units, experiences of teaching students with special needs, and teacher training on inclusive education on teacher self-efficacy in the inclusive education context. The participants of this study were 233 teachers, in which most of them were women and had master's degrees. For the data analysis, we used Multi-Variate Analysis of Variance (MANOVA). This study concludes that only the teacher work unit variable induces different teacher self-efficacy scores. Teachers in elementary schools have the highest self-efficacy scores in instruction, collaboration, and managing behaviour efficacy.